PENYULUHAN PENGEMBANGAN IDE KREATIF GUNA MENINGKATKAN MINAT WIRAUSAHA SMA VIANNEY JAKARTA - Louis Utama; Vivian Julianti Huang; Mudita Hung Dharma Putri; Devinia Renata; Priscilla Aurelia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2026)
The younger generation, as aspiring entrepreneurs, particularly in the creative economy sector, is expected to possess intrinsic skills, including creative ideas and innovativeness, as well as the ability to utilize technology. Implementing a culture of innovation within an organization is a strategic step towards achieving competitive advantage. In achieving this goal, communities often encounter obstacles, one of which is a reliance on traditions and existing methods, thus neglecting innovation. The current generation is expected to become a competitive and value-added generation by developing and driving the creative economy. Education is needed for the public and the younger generation, especially high school students, regarding innovation in the creative economy, which opens up significant opportunities for young people to advance the creative sector in Indonesia. The program's partners are students from Vianney High School in West Jakarta. The problem faced is a lack of creative thinking among students, resulting in a lack of innovation in the student council's work program. This outreach program is expected to foster creative traits, leading to numerous innovations that can increase entrepreneurial intentions. Generasi muda yang merupakan calon wirausaha khususnya atas sektor ekonomi kreatif diharapkan mempunyai keahlian dari dalam diri sendiri yaitu ide kreatif, inovatif dan serta kemampuan dalam menggunakan teknologi. Menerapkan budaya inovasi terhadap sebuah organisasi merupakan langkah strategis untuk mencapai keunggulan kompetitif. Dalam mencapai tahapan ini, masyarakat seringkali mendapatkan hambatan salah satunya adalah masih bergantung pada tradisi dan metode yang telah ada sehingga mengabaikan adanya inovasi. Generasi muda saat ini diharapkan menjadikan generasi yang berdaya saing dan memiliki nilai tambah adalah dengan menumbuhkan dan menggerakkan ekonomi kreatif. Perlunya edukasi kepada masyarakat dan generasi muda khususnya siswa SMA mengenai inovasi tentang ekonomi kreatif yang membuka peluang besar bagi generasi muda untuk memajukan sektor kreatif di Indonesia. Mitra dalam program ini adalah siswa SMA Vianney Jakarta Barat. Masalah yang dihadapi adalah kurangnya pemikiran kreatif yang dimiliki oleh siswa sehingga kurangnya inovasi dalam program kerja OSIS. Dengan adanya program penyuluhan ini diharapkan dapat mengembangkan sifat kreatif sehingga dapat menimbulkan banyak inovasi yang dapat menambah niat menjadi wirausaha.